Strategic Sales Performance in Pahlawan Lake Resort - Adam, Mohd Saifudin (College of Business Universiti Utara Malaysia, 2009)
Pahlawan Lake Resort, under the management of Paka Utama Holdings Sdn Bhd, is focused to project itself to become the best rural tourism destination in Kedah State and and best tourist hub for Northern Region of Malaysia. Paka Utama Holdings Sdn Bhd is awarded a 20 years leasing of land of Pahlawan Lake, a 25 km distance from Alor Setar, a capital of State of Kedah and a 5 km distance from Jitra township, dated 15 Mac 2006. Since then, major activities are planned and implemented with major ones are the building and facilities construction since 2007, with more than RM 8 million being spent to re-launch or re-branding and up-grading the resort to meet the expectations of the management as the best tourists destination for northern region. Full constructions of the facilities and buildings are expected to be completed fully by end of 2009. But as the business too need to be run at the same time, the sales progress are not encouraging even though much efforts are put into the promotions and advertisements, especially through the internet, brochures and tourism networks. It is ironic that there are an increasing flow of foreign tourists to Malaysia since 1998 to 2008 but the tourists’ destinations such as Pahlawan Lake Resort is almost insignificant in the context of tourists’ attractiveness. This caused some discontentment over the focused plan and how the plan is being implemented as only 20 to 30 percent of the total sales forecasted had been achieved so far. Thus, this consultation project intends to provide Pahlawan Lake Resort with plans and strategies after carefully examine and analyze their Porter’s 5 Forces of Strategic Plan as the main model of the study; and internal and external factors of their strengths, weaknesses,opportunities and threats (SWOT Analysis). The internal analyses of strengths and weaknesses would examine the resort from the following aspects - management, finance, human resources, marketing,organizational image, cost, location, facilities/infrastructure, number of tourists (local, domestics and foreigners) and government assistant. Meanwhile, the external analyses would examine the resort opportunities and threats factors such as economy, competitiveness, customers’ trend,technology, legal, and market structures.Based on Porter’s 5 Forces Model and SWOT analyses, it is found that the resort unable to seize opportunities available in the external environment if their internal weaknesses are left unattended and the internal strengths are simply not upgraded. Thus, recommendations are given based on its strategic sales planning and appropriateness of execution. Nonetheless, the recommended strategies would serve as roadmap for the resort to achieve as their favorite tourists’ destination target and become the best tourists’ hub for Northern Region of Malaysia.Thus this will provide the resort to become self-sufficient in future for any other plan that they intend to explore.